Percepción docente sobre los procesos de lectoescritura en estudiantes de cuatro niveles educativos - Vázquez Reyes, Óscar Martín (2024)
This study addresses literacy from the perspective of 12 Mexican teachers from various educational levels, with the objective of understanding their opinions on the factors that affect the teaching-learning process. With a qualitative approach and a phenomenological design, in-depth interviews were conducted which revealed a widespread perception of lagging literacy skills and poor student performance, from elementary school to university. Teachers attribute this problem to various factors, such as the lack of specialized teacher training, inadequate educational plans and programs, the socio-family context of the students, and the excessive use of technological devices. They also highlight the importance of feedback and motivation in the teaching process, and the need for continuous formative assessment. This study confirms the need to strengthen literacy training and to design educational plans and programs that respond to the real needs of the students, promoting the development of these essential skills from an early age.